PTH-030 Esge survey: practice patterns amongst european gastroenterologists regarding the endoscopic management of barrett's oesophagus. (22nd June 2015) - Dunn, S; Neilson, L; Hassan, C; Sharma, P; Guy, C; Rees, C
Abstract : Introduction: Barrett's Oesophagus is a common condition that is widely encountered in clinical practice. This European Society of Gastrointestinal Endoscopy (ESGE) survey asked clinicians attending United European Gastroenterology Week (UEGW) 2014 in Vienna to answer questions about their practice in the diagnosis and management of Barrett's Oesophagus. Method: A ten question survey was programmed on to two iPads and delegates attending the ESGE learning area were asked to complete it. The information gathered was demographics, practice settings and management strategies for Barrett's Oesophagus. This survey was based on a similar survey done in the USA in 2013, 1 and was carried out as an ESGE initiative on behalf of the ESGE research committee. Permission was obtained from the original author of the American survey to reproduce it in a European setting. Results: 163 responses were obtained. Over half of respondents (61%) were based in university hospitals, the majority (78%) were aged 30–50 and half had more than ten years' experience in gastroenterology. 66% routinely attended courses on Barrett's Oesophagus and more than half (60%) used the Prague C&M classification. Advanced imaging was used by 73% of clinicians and 72% of respondents stated that their group practiced ablation therapy. Most (76%) practiced surveillance for non-dysplastic Barrett's, 6% offered ablation therapy in some situations and 18% offered no intervention. For low grade dysplasia 56% practiced surveillance, 19% ablated some cases and 15% ablated all cases. 32% of clinicians referred high grade dysplasia to expert centres, 20% referred directly for surgery and 46% used ablation therapy in certain cases. Endoscopic mucosal resection was the most commonly used ablation technique (44%). Conclusion: There has been good uptake of the Prague C&M classification for describing Barrett's Oesophagus and ablation is widely practiced. However practice patterns in the endoscopic diagnosis and management of Barrett's Oesophagus vary widely between clinicians. Clear guidance and quality standards are therefore required. Disclosure of interest: None Declared. Reference: Singh M, Gupta N, Gaddam S, Balasubramanian G, Wani S, Sinh P, et al . Practice patterns among US gastroenterologists regarding endoscopic management of Barrett's esophagus. Gastrointestinal Endoscopy 2013;78(5):689–95